GEOACOUSTIC EMISSION AT YANOSHI OBSERVATION POINT, TRANSCARPATHIANS - Malytskyy, D.; Nazarevych, A.; Mikita, A.; Astashkina, O.; Koval', Yu.; Makhnitskyy, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper highlights the methodological and practical aspects of the continuous automated system of geoacoustic observations for controlling and predicting local geodynamic processes. It is a well-established scientific fact that geoacoustic emission signal generation observed in the surface area is associated with the formation of cracks relating to the build up of an earthquake. The study of geoacoustic emission signals is therefore of practical value for creating an inexpensive rapid earthquake prediction system. To make geoacoustic observations we used modified digital mine equipment SCA-6 (which was improved to extend the frequency range of the recorded signals), Sound Blaster sound card and PowerGraph laptop software for data recording. The dataset analysis included creating and interpreting a graph of geoacoustic intensity variation (the number of events in a given time interval) and comparing it with the data on the local scale seismic events that occurred during the observation period. The geoacoustic research conducted in 2014 at the Yanoshi observation point near Berehove station yielded data on significant changes in the general emission levels associated with the local geoacoustic field (an increase in the number of daily intensive events). In the time series, the acoustic rock activity reached a noticeable peak in the 20th of April, with a further significant and sustained increase in such activity being observed from the second half of May until early September. Increased geoacoustic emissions coincided in time with a small local earthquake that took place on June 7, 2014 near the village of Fornosh, south of Mukachevo, at a distance of approximately 17 km from the observation point. The correlation between the seismic and geoacoustic emission events that occurred close in time suggests their relationship and proves the feasibility of using geoacoustic seismic observations in earthquake prediction studies.